The Impact of FinTech and Artificial Intelligence (AI) Adoption on the Stability and Profitability of Islamic Banking: A Systematic Literature Review - Zainudin, Muhammad; Hidayatulloh, Muhammad Haris (MALIA: Journal of Islamic Banking and Finance, 2025)
This study aims to systematically synthesize the latest literature (2019–2025) on the impact of the adoption of Financial Technology (FinTech) and Artificial Intelligence (AI) on the stability and profitability of Islamic banking, in response to a significant wave of digital disruption. Through the Systematic Literature Review (SLR) methodology, the results of bibliometric mapping show a high surge in publication volume, dominated by core authors from dual banking system regions such as Indonesia, Malaysia, and MENA, confirming the urgency of this topic. A synthesis of the findings shows that the adoption of FinTech and AI has a positive correlation with increased systemic stability benefits for Islamic banks, a phenomenon associated with the unique role of their strong governance and asset-based financing structures. However, the research agenda has shifted thematically from traditional micro-operational issues (efficiency, liquidity) to more strategic and systemic clusters of innovation. This innovation cluster focuses on macroeconomic resilience (mitigating external risks such as global economic policy uncertainty) and the challenges of ethical value model innovation (including new digital compliance costs and the need for Sharia-compliant integration). In conclusion, Shariah banking is faced with a mandate to achieve three-dimensional resilience: micro-operational, digital-ethical, and macro-systemic. This study contributes by providing a comprehensive and integrated literature map as a strategic guide for regulators and practitioners.